Van Neck-Odelberg Disease — A Rare or Underdiagnosed Condition? - Moreira, Mafalda; Alba, Diana; Nogueira, Hélder; Teixeira, Sandra (Revista Brasileira de Ortopedia, 2022)
Van Neck-Odelberg (VNO) disease is a rare osteochondrosis affecting the ischiopubic synchondrosis (IPS). This condition should be included in the differential diagnosis of children with lameness, inguinal pain, and functional limitation of the hip. In imaging tests, it is characterized by asymmetric IPS hypertrophy. We present the clinical case of a 4-year-old child, previously healthy, who visited the emergency department for left inguinal pain and lameness starting on the same day. There was no previous history of trauma or changes in inflammatory parameters. The patient underwent a pelvic radiography and magnetic resonance imaging (MRI), which revealed a radiopaque image with well-defined contours in the left ischiopubic branch, and IPS swelling. With a presumed diagnosis of VNO disease, the patient was medicated symptomatically, with complete recovery in 10 days. Lameness is a frequent reason for medical evaluation in the pediatric population. In subjects up to 5 years old, the most common causes of lameness include transient hip synovitis, septic arthritis, and Legg-Calvé-Perthes disease. In the absence of a history of trauma or infection-related clinical findings, VNO disease should be considered as a hypothesis. Its diagnosis requires a pelvic radiography, usually showing a unilateral fusiform opacification at the ischial level; an MRI may be necessary. The recommended treatment is conservative, with symptomatic recovery in 2 weeks. The knowledge and diagnosis of VNO disease allow a targeted approach, without the emotional burden for the patient and his/her family that may be associated to other conditions.
Keywords: child; intermittent claudication; osteochondrosis